2020
DOI: 10.21203/rs.3.rs-54127/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells transfer in patients with ST-segment elevation myocardial infarction: single-blind, randomized controlled muticentre trial

Abstract: Objective: Our aimed to evaluate efficacy and safety of intracoronary autologous bone morrow mesenchymal stem cells (BM-MSCs) transplantation in patients with ST-segment elevation myocardial infarction(STEMI). Methods: In this randomised, single-blind, controlled trial, patients with STEMI (aged 39-76 years) were enrolled at 6 centers in Beijing (the People's Liberation Army Navy General Hospital, Beijing Armed Police General Hospital, Chinese People's Liberation Army General Hospital, Beijing Huaxin Hospital,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In this meta-analysis, we found that MSCs therapy within 2-14 days after PCI was more effective than MSCs transplantation within 2 days or 14 days after PCI. The results of present study also explain the negative results of our previous clinical trials [23]. The reason for the negative results of transplantation within 2 days after myocardial infarction may be due to the bad local microenvironment such as in ammation, which caused the death of a large number of transplanted cells, thereby affecting the transplantation effect.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In this meta-analysis, we found that MSCs therapy within 2-14 days after PCI was more effective than MSCs transplantation within 2 days or 14 days after PCI. The results of present study also explain the negative results of our previous clinical trials [23]. The reason for the negative results of transplantation within 2 days after myocardial infarction may be due to the bad local microenvironment such as in ammation, which caused the death of a large number of transplanted cells, thereby affecting the transplantation effect.…”
Section: Discussionsupporting
confidence: 58%
“…The results of several clinical studies have shown that high-dose MSCs (10 8 cells) were more effective in improving LVEF [28,29]. In our previous clinical studies, the use of low cell doses (< 10 7 cells) did not nd signi cant improvement in cardiac function [23]. Our meta-analysis results indicate that the optimal therapeutic dose of MSCs cell therapy may be 10 7~1 0 8 cells.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations